Acid‐Cleavable Poly(ethylene glycol) Hydrogels Displaying Protein Release at pH 5. Issue 13 (18th February 2020) - Ewald, Johannes; Blankenburg, Jan; Worm, Matthias; Besch, Laura; Unger, Ronald E.; Tremel, Wolfgang; Frey, Holger; Pohlit, Hannah
Abstract: PEG is the gold standard polymer for pharmaceutical applications, however it lacks degradability. Degradation under physiologically relevant pH as present in endolysosomes, cancerous and inflammatory tissues is crucial for many areas. The authors present anionic ring‐opening copolymerization of ethylene oxide with 3, 4‐epoxy‐1‐butene (EPB) and subsequent modification to introduce acid‐degradable vinyl ether groups as well as methacrylate (MA) units, enabling radical cross‐linking. Copolymers with different molar ratios of EPB, molecular weights ( M n ) up to 10 000 g mol −1 and narrow dispersities ( Đ <1.05) were prepared. Both the P(EG‐ co ‐ iso EPB)MA copolymer and the hydrogels showed pH‐dependent, rapid hydrolysis at pH 5–6 and long‐term storage stability at neutral pH (pH 7.4). By designing the degree of polymerization and content of degradable vinyl ether groups, the release time of an entrapped protein OVA‐Alexa488 can be tailored from a few hours to several days (hydrolysis half‐life time t 1 /2 at pH 5: 13 h to 51 h). Abstract : Responsive gels : P(EG‐ co ‐ iso EPB)MA, a PEG copolymer with acidic degradability under physiologically relevant pH is employed for hydrogels. The attached methacrylate units enable radical cross‐linking to form protein‐loaded hydrogels. Both the P(EG‐ co ‐ iso EPB)MA copolymer as well as the respective hydrogels show rapid and tailorable hydrolysis at physiologically relevant pH (pH 5–6), despite excellent storage stability at neutral pH (pH 7.4).